Sosialisasi Perilaku Hidup Bersih dan Sehat (PHBS) di Lingkungan Panti Asuhan Mizan Amanah - Ardhiasti, Anggi; Akbar, Prima Soultoni; ingrum, Herlinda Dwi N (Yayasan Daarul Huda Kruengmane, 2024)
One of the causes of low PHBS scores in schools is due to students' lack of knowledge about the importance of clean and healthy living. By implementing PHBS in orphanages by students, teachers and the local community, it will form them to have the ability and independence to prevent disease, improve their health and play an active role in creating a healthy orphanage and school environment. The aim of this activity is to provide education to students living at the Mizan Amanah Malang Orphanage regarding Clean and Healthy Living Behavior (PHBS). The methods used are lectures, discussions, questions and answers and games. The results of the activity were an increase in the knowledge and understanding of students living at the Mizan Amanah Malang Orphanage regarding PHBS. The output of this activity is a PHBS prevention guidebook.